3, 4‐Dihydroxyphenylethanol and 3, 4‐dihydroxyphenylacetic acid affect the aggregation process of E46K variant of α‐synuclein at different extent: Insights into the interplay between protein dynamics and catechol effect. (16th June 2022) - Fongaro, Benedetta; Cappelletto, Elia; Sosic, Alice; Spolaore, Barbara; Polverino de Laureto, Patrizia
Abstract: Parkinson's disease (PD) is a chronic multifactorial disease, whose etiology is not completely understood. The amyloid aggregation of α‐synuclein (Syn) is considered a major cause in the development of the disease. The presence of genetic mutations can boost the aggregation of the protein and the likelihood to develop PD. These mutations can lead to early onset (A30P, E46K, and A53T) or late‐onset (H50Q) forms of PD. The disease is also linked to an increase in oxidative stress and altered levels of dopamine metabolites. The molecular interaction of these molecules with Syn has been previously studied, while their effect on the pathological mutant structure and function is not completely clarified. By using biochemical and biophysical approaches, here we have studied the interaction of the familial variant E46K with two dopamine‐derived catechols, 3, 4‐dihydroxyphenylacetic acid and 3, 4‐dihydroxyphenylethanol. We show that the presence of these catechols causes a decrease in the formation of amyloid fibrils in a dose‐dependent manner. Native‐ and Hydrogen/deuterium exchange‐mass spectrometry (HDX‐MS) provide evidence that this effect is strongly conformation dependent. Indeed, these molecules interact differently with the interconverting conformers of Syn and its familial variant E46K in solution, selecting the most prone‐to‐aggregation one, confining it into an off‐pathway oligomer. These findings suggest that catechols could be a molecular scaffold for the design of compounds potentially useful in the treatment of Parkinson's disease and related conditions.